Respuesta :

Answer:

See graph

Step-by-step explanation:

We want to graph the function [tex]f(x)=x^2-2x-3[/tex].


Let us rewrite this function in the vertex form so that we can graph it easily.


We achieve this by completing the square as follows;


[tex]f(x)=x^2-2x+(-1)^2-(-1)^2-3[/tex]


[tex]\Rightarrow f(x)=(x-1)^2-1-3[/tex].


[tex]\Rightarrow f(x)=(x-1)^2-4[/tex].


Comparing to  [tex]f(x)=a(x-h)^2+k[/tex],  we have [tex]a=1\:>\:0[/tex],this means the graph will open up.

where [tex](h,k)=(1,4)[/tex] is the vertex of the quadratic graph.

To find the y-intercept we put [tex]x=0[/tex] into the function to get,

[tex]f(0)=(0-1)^2-4=-3[/tex].


To find the x-intercept, we put [tex]f(x)=0[/tex].

[tex](x-1)^2-4=0[/tex].


[tex](x-1)^2=4[/tex].


[tex]x-1=\pm \sqrt{4}[/tex].


[tex]x-1=\pm 2[/tex].


[tex]x=1\pm2[/tex].


[tex]x=-1,x=3[/tex]


With the nature of graph in mind, taking into consideration, the vertex and the intercepts, we draw the graph to obtain the quadratic graph in the attachment.




Ver imagen kudzordzifrancis
ACCESS MORE